2016
DOI: 10.1186/s13072-016-0081-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and inheritance of phenotype variation in livestock

Abstract: Epigenetic inheritance plays a crucial role in many biological processes, such as gene expression in early embryo development, imprinting and the silencing of transposons. It has recently been established that epigenetic effects can be inherited from one generation to the next. Here, we review examples of epigenetic mechanisms governing animal phenotype and behaviour, and we discuss the importance of these findings in respect to animal studies, and livestock in general. Epigenetic parameters orchestrating tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 199 publications
(210 reference statements)
1
63
0
4
Order By: Relevance
“…growth and development (Sanchez & Schoch 2013;Tobi et al 2014;Triantaphyllopoulos et al 2016). Finally, an increasing number of genome-wide studies suggest that slight changes to small portions of a species' genome can alter the phenotype of key adaptive traits, such as plumage coloration (e.g.…”
Section: Causes Of Conflict Between Molecular and Phenotypic Datamentioning
confidence: 99%
“…growth and development (Sanchez & Schoch 2013;Tobi et al 2014;Triantaphyllopoulos et al 2016). Finally, an increasing number of genome-wide studies suggest that slight changes to small portions of a species' genome can alter the phenotype of key adaptive traits, such as plumage coloration (e.g.…”
Section: Causes Of Conflict Between Molecular and Phenotypic Datamentioning
confidence: 99%
“…However, quantitative trait analyses and genome-wide association studies have shown that genetic variation is not the only contributor to phenotypic variability [1]. An increasing number of evidence suggests that epigenetics may also contribute to the phenotypic diversity of animals, in interaction with their environment [2]. Recently, epigenetic reprogramming of gene expression was shown to impact, in the long term, the phenotypes of birds.…”
Section: Introductionmentioning
confidence: 99%
“…This pleads for a very careful choice of embryo recipients in terms of breed and size but also underlines the importance of the management of these animals before and during pregnancy. The molecular basis for these effects is epigenetic mechanisms (Gonzalez-Recio et al, 2015;Triantaphyllopoulos et al, 2016). Future research is needed to explore if epigenetic markers could be used as predictors of long term outcomes in offspring.…”
Section: Practical Implications For Embryo Transfermentioning
confidence: 99%